Efeitos do PECS associado ao video modeling em crianças com síndrome de Down - Rodrigues, Viviane (Universidade Federal de São Carlos, 2015)
The Augmentative and Aumentative Communication (AAC) is an area of assistive technology that seeks to facilitate the participation of people in different communicative contexts. There is a variety of techniques and methods one of them Picture Exchange Communication (PECS) that proposes to develop communication skills within the social context. Associated with the implementation of PECS, some research has shown benefits of using Video Modeling (VM) that consists a teaching technique that search the development of academic, social, communication and daily leaving skills for individuals of various disabilities. The objective of this study was to apply and analyze the effects of PECS associated with the VM on the development of communication skills of children with Down syndrome. To this end, we selected three participants in a special school in one city in the state of São Paulo, aged between nine and 12 who were diagnosed as Down syndrome and complex communication needs. The following instruments were used in this study: Assessment of Communication Skills was used to evaluate functional communication skills the child; Protocol for Communication Skills Assessment in a school environment with the objective to identify the communication skills of the student in the school environment from the perception of teachers; Vocabulary selection spread sheet with the objective to identify reinforcing objects; Record Sheet that informed participants' performance during the intervention process; Vocabulary sheet monitored the vocabulary of the participants during the intervention; Chart Qualitative Performance was used as a field diary in order to record observations during the intervention process and the Social Validity of questionnaire with the objective to evaluate the perceptions of parents and teachers of the participants about the intervention. In order to verify the effects of the intervention it used Multiple Baseline Design cross subjects including three phases: baseline, intervention, and maintenance, in which the PECS associated with the VM was the independent variable and communication skills constituted the dependent variable. Data were analyzed considering some aspects such as the participant's performance, monitoring vocabulary, level of independence in the baseline, intervention and maintenance steps. The results showed that participants' performance was satisfactory both in respect of each phase and with respect to all the learning process intervention. The level of independence remained above average throughout the training for the three participants, in other words, they understood what they must do in each session of each phase without the aid of the communication partner or physical stimulator. There was an increase in the vocabulary of the three participants, although each of them with his own specificities and development of language, it is noted that the use of the pictures served as a support for the increase in this vocabulary words and phrases formulations through both figures as through speech. Thus, the present study showed a possibility of intervention that favored the participants with Down syndrome, demonstrating that the PECS associated with the VM promoted the development of communication skills, both in speech production as in the use of the figure as a form of communication.
Keywords: Educação especial; Tecnologia assistiva; Down, Síndrome de; Comunicação suplementar e alternativa; Sistema de comunicação por troca de figuras; Special education; Augmentative and alternative communication; Down syndrome; Picture exchange communication system; Video modeling; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL